2016
DOI: 10.1186/s13098-016-0181-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of diabetes in Brazil over time: a systematic review with meta-analysis

Abstract: Diabetes is one of the most important epidemic diseases of this century and the number of people with diabetes has more than doubled over the past three decades. Our aim was to estimate the prevalence of diabetes in the adult Brazilian population and analyze the trends for the last three decades through a systematic review with meta-analysis. This review included observational studies published between 1980 and 2015, which were independently identified by two reviewers in five databases. Random effect models w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
1
19

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 68 publications
4
44
1
19
Order By: Relevance
“…12 This study was the first school-based report in Latin America to estimate the prevalence of T2DM and prediabetes among youth. Our results indicate that T2DM has reached epidemic proportions not only in adults, 5 but also in adolescents in Brazil. Extrapolation of our results to the adolescent population in cities with more than 100 000 inhabitants resulted in 200 000 living with T2DM and almost 1.5 million with prediabetes, a condition that has been shown to increase cardiovascular risk in this population.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…12 This study was the first school-based report in Latin America to estimate the prevalence of T2DM and prediabetes among youth. Our results indicate that T2DM has reached epidemic proportions not only in adults, 5 but also in adolescents in Brazil. Extrapolation of our results to the adolescent population in cities with more than 100 000 inhabitants resulted in 200 000 living with T2DM and almost 1.5 million with prediabetes, a condition that has been shown to increase cardiovascular risk in this population.…”
Section: Discussionmentioning
confidence: 62%
“…Extrapolation of our results to the adolescent population in cities with more than 100 000 inhabitants resulted in 200 000 living with T2DM and almost 1.5 million with prediabetes, a condition that has been shown to increase cardiovascular risk in this population . Several previous studies have reported a rapid increase in the prevalence of diabetes in Brazil, mostly in adults . However, most of these studies were based on self‐reports.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Has a total population of 206 million inhabitants with a life expectancy of 74.8 years 13 . Diabetes prevalence is 8.68% (equivalent to 11.6 million people with diabetes); with this figure Brazil is the 4 th nation in terms of number of people with diabetes in the world, just after China, India and the USA 14,15 .…”
Section: Brazilmentioning
confidence: 99%
“…Not all people with diabetes have yearly control of HbA1c and not all the laboratories in the country use for its measurement methods certified by the National Glycohemoglobin Standardization Program (NGSP) 13 .…”
Section: Argentinamentioning
confidence: 99%